Operator Exposure to Whole-Body Vibration in Timber Extraction with Grapple Skidder - Cazani, Ana C [UNESP]; Miyajima, Ricardo H [UNESP]; Simões, Danilo [UNESP]; dos Santos, João E G [UNESP] (Springer Nature, 2020)
Purpose: The objective was to evaluate the occupational vibration acting under grapple skidder operators during skidding operation of the Eucalyptus tree bundles. Methods: The collection of the whole-body vibration data was based on the methodology recommended by the International Organization for Standardization (ISO 8041 and ISO 2631). Then, technical procedure for obtaining vibration data from the operators was performed using a Larson Davis tri-axial vibration meter, model HVM 200 and a tri-axial ICP accelerometer of the seat pad type. Results: When comparing the values of the weighted acceleration and VDV with the limits established by the European Directive, it is verified that in both tests, the measured values are higher than the one expected by the respective regulation. Compared to the ISO 2631 criteria, both tests provided results located in the danger zone. Conclusion: The values obtained indicate that occupational exposure may cause health risks to grapple skidder operators. The results showed the need of actions that can minimize the transmission of vibration to the operators due to the level being above the guidelines, despite all the technology used by manufacturers of machinery for harvesting.
Keywords: Ergonomics; Forest operation; Lumbar disc disease; Mechanical vibration; Musculoskeletal injury; Occupational health